Improvement of an independent curriculum learning model via community service mentoring - Nuriah, Yuyun; Haratua, Chandra Sagul; Komari, Komari (Indonesian Research Journal in Education |IRJE|, 2025)
This research aimed to identify and obtain information regarding implementing the independent curriculum learning model in schools. The research employed an action research approach to enhance the implementation of the independent curriculum learning model by facilitating a Community Service Program (Abdimas). The research results indicated that the independent curriculum learning model improved teacher performance over three mentoring cycles. In cycle 1, teachers' understanding of the national curriculum policy increased to 78.2%, and understanding of the national curriculum implementation reached 74%, indicating a notable improvement from the pre-cycle phase. In cycle 2, further increases were recorded: understanding of learning objective flow rose to 79.42%, understanding of the learning model reached 88.4%, and understanding of the teaching module reached 87.8%, reflecting nearly optimal mastery. In cycle 3, teachers' comprehension regarding the practice of learning models attained 88.6%, signaling their capability to implement effective classroom instruction.